Urgensi Manajemen Budaya Organisasi Sekolah Terhadap Pembentukan Karakter Peserta Didik: The Urgency of School Organizational Culture Management Against Character Building Students - Rony Rony (Tafkir: Interdisciplinary Journal of Islamic Education, 2021)
To improve the quality of human resources (human resources development) in order to be able to keep up with developments in science and technology, people tend to choose quality educational institutions. The quality of education in schools is inseparable from the culture of the school organization which has become a distinct character of education in schools. In addition to functioning as a school identity that differentiates schools from one another, it can be a standard of behavior for school members that influence school members to carry out internalized actions. The development of a strong, intimate, conducive, and responsible school organizational culture will provide various benefits for all school members. Every school member must play an active role in developing and realizing a good school culture. To develop and create a school organizational culture that can shape the character of students is not an easy matter. In addition to several supporting factors that can help the implementation of a good school organizational culture, there are also inhibiting factors that cannot be underestimated, which will cause the implementation of school organizational culture management not to be carried out properly.